2018
DOI: 10.1016/j.drugalcdep.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and engagement as mechanisms for change caused by collaborative care in opioid and alcohol use disorders

Abstract: Among primary care patients with OAUDs, treatment initiation partially mediated the effect of CC on abstinence at 6-months. The current study emphasizes the importance of primary care patients returning for a second substance-use related visit after identification. CC may work differently for people with co-morbid opioid use disorders vs. alcohol use disorders alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Using mediation analysis, we found that the pathway from medication assignment (and subsequent initiation) through mediators of adherence, early illicit opioid use, depressive symptoms and pain contributed to much of the increased risk of relapse on XR-NTX versus BUP-NX for non-homeless participants, but did not substantially contribute to the reduced risk of relapse among homeless participants. Despite the importance of mediation analyses in understanding the different ways in which medications can improve patient outcomes, there have been few such analyses for OUD treatment [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Using mediation analysis, we found that the pathway from medication assignment (and subsequent initiation) through mediators of adherence, early illicit opioid use, depressive symptoms and pain contributed to much of the increased risk of relapse on XR-NTX versus BUP-NX for non-homeless participants, but did not substantially contribute to the reduced risk of relapse among homeless participants. Despite the importance of mediation analyses in understanding the different ways in which medications can improve patient outcomes, there have been few such analyses for OUD treatment [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not include a control group taking other pharmacological interventions for alcohol use disorder, such as acamprosate, disulfiram, gabapentin, topiramate, or a placebo [15]. In addition, we only included male individuals, and the alcohol-use clinical outcome assessment was based on self-report only; this was based on methodology suggested in recent randomized clinical prospective studies [47][48][49][50]. Interestingly, this study genotyped 100 individuals with AUD for four genotype variants of interest [14,51,52], as well as analyzed their association with the clinical assessment measures during a standardized 12-week treatment, based on an FDA approved intervention [53] and an intention-to-treat analysis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative care can support the management of comorbidities in primary care while complex AoD issues are managed in the specialist AoD setting. This may lead to greater engagement in care and improved health outcomes (Setodji et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that specialist AoD and general practice collaborative care would support AoD treatment (Samet et al 2001;Weisner et al 2001), but studies are limited. US studies have shown increased utilisation of treatment services (Setodji et al 2018) and improved abstinence (Samet et al 2003;Watkins et al 2017) following collaborative care. The use of patient-reported health and well-being outcomes is limited in these studies and it is unclear what aspect of the interventions in the heterogeneous studies led to this effectiveness (Pace and Uebelacker 2018).…”
Section: Introductionmentioning
confidence: 99%